Spin-selective reactions of radical pairs act as quantum measurements - Jones, J; Hore, P (Elsevier, 2010)
Since the 1970s, spin-selective reactions of radical pairs have been modelled theoretically by adding phenomenological rate equations to the quantum mechanical equation of motion of the radical pair spin density matrix. Here, using a quantum measurement approach, we derive an alternative set of rate expressions which predict a faster decay of coherent superpositions of the singlet and triplet radical pair states. The difference between the two results, however, is not dramatic and would probably be difficult to distinguish experimentally from decoherence arising from other sources.